Curriculum-based evaluation : teaching and decision making - Howell, Kenneth W. (Wadsworth, 2000)
Educational decision making. Thinking about learning. Thinking about the curriculum. Thinking about instruction. Fundamentals of evaluation. Tools for assessment. Problem-solving evaluation and decision making. Reading comprehension. Decoding. Language...